Local scour at piled bridge piers including an examination of the superposition method - Amini, Ata; Melville, Bruce William; Mohamed Ali, Thamer Ahmad (NRC Research Press, 2014)
An experimental investigation of clear water scour at complex piers is presented. Five complex piers, comprising different configurations of piles, pile cap, and column, were tested in a laboratory flume using uniform bed material. The piers were tested for a range of possible elevations relative to the streambed elevation. Experiments were undertaken using the complex piers and also using the individual components of each complex pier. A comparison of the results for the intact piers and for their components enabled an evaluation of the prediction methods involving superposition of scour depths at piles, pile cap, and pier column. The superposition method is found to give inadequate estimates of total scour depth in many cases.